Place-making strategies of culturepreneurs. The case of Frankfurt/M., Germany - Bastian Lange (European Regional Science Association (ERSA), 2002)
The paper describes the emergence of a new hybrid cultural and entrepreneurial agent in the context of the local cultural industries of Frankfurt on Main (Germany). The thesis of the paper is, that the culturepreneur is responsible for new place-making strategies apart the most visible and dominant one, such as the skyline in Frankfurt/M. The understandings of his place-making strategies offer insights in new forms of negotiation of an urban renewal process. Despite this it provides a new and important evaluation of the yet underestimated spatial category place in the process and formation of scenes, recently brought into discussion by sociologist R. Hitzler (2001). Places are the terrain of the post-industrial city where different and heterogeneous scenes are struggling. The analysis of the use and significance - out of the perspective of culturepreneurs - provides a new, yet in the field of social sciences unclear, reading of the existing urban condition. The context of the emergence of the type culturepreneur is framed by neoliberal governmental and political approaches, urban marketing campaigns such as the self-promotion as being a young and a cool city like Frankfurt/M. (or Berlin) are practicing it, in order to encourage individuals to launch ones own enterprise: The first results can best be seen in the field of the growing numbers of workers in the socalled creative (service-industry-related) sector. Besides that, the growing numbers of creatives, such as web-, fashion-, music and arts and crafts designers as well as club organizers are - viewed from an institutional perspective - an expression of complex changes of the role of the arts and media sector as growing mediator between the subsectors of culture and economy. Based on comparable results of A. McRobbie's studies (1999) in the creative sector of London (GB), this research shows that the agents of creative work are - especially since 1998 - on the one hand considered to be a symbolic forerunner and a pioneer of the politics of the new middle in Germany ('Politik der Neuen Mitte'). Thereby on a micro level we can observe agents, who reflect increasing values such as individual entrepreneuralism, bringing to light un-embedded as well as flexible labour situations. Besides their escalating sharp existential situation, they show a rising dependency of subsidies of different sponsors. Thereby creative work is squeezed and brokered by growing influences of venture capitalists using trendy popular culture products of the culturepreneurs as signs and symbols of their holistic idea serving the society. On the other hand, the growing numbers of relatively young and creative workers struggle to regain social and institutional embedding by setting up and creating new temporary and flexible alliances with different agents in the urban context, such as city governments as well as corporate firms. In sociological terms we cannot consider these actors as members of a completely individualized society anymore (Beck 2000), but as members of post-traditional communities or, like Hitzler proposed, new scenes (Hitzler 2001) amongst the culturepreneur plays a key and ma-jor formatting role, which is yet from the scientific perspective so far undefined. The paper argues that the analysis of the local cultural industry as a key factor in the creation of new labour forces in the metropolitan regions such as the Rhine-Main as well as stimulating atmospheres for service-related industries has to be connected to micro-spatial analysis of the emergence of new scenes. Sociological analysis provides valuable insights in the formation of new communities, but micro-geographical analysis can conceptually and methodologically provide a spatial understanding of complex place-making strategies of new post-traditional communities. Space is a yet an underestimated variable in the analysis of the emergence of new agents - such as the culturepreneurs - in the field of the local cultural industries. The conducted field research shows not only the fact that - from the perspective of individual agents (culturepreneurs) - place matters, but that the processes of professional socialisation is closely linked to a complex creative and necessarily practice with place in order to create a spatial network, that means a new socially-defined space. This process can first be seen as a necessary attempt in order to regain a professional place in the labour market, but second as a practice to get economic, social, and network-related attention by acting, staging and using (with) the variable place. Culturepreneurs develop - with new forms in the field of the economy of attention - these new geographies that can be read as a post-modern counterstrategy to the dominant place-making strategies, applied most visible with the geography of centrality in the case of Mainhatten (sic!), Frankfurt on Main.
Keywords: 330